A Retrospective Study of Serum Calcium Status in Tehran, Iran (105,128 Samples, from 2009-2018) - Dariush D. Farhud; Marjan Zarif-Yeganeh; Atefeh Mehrabi; Ali-Reza Afshari; Mohammad Bagher Rokni; Keyvan Majidi; Maryam Jalali; Ali Akbar Amir Zargar; Abdolfattah Sarafnejad; Hamid Reza Sadeghipour; Shaghayegh Zokaei; Farideh Khosravi; et al. (Tehran University of Medical Sciences, 2022)
Background: Calcium is a necessary mineral for life to keep the body and bones healthy. Various factors including hormones, diet, age, and gender affect serum calcium status. The aim of this sturdy was to assess the serum calcium level (SCL) of Tehran population, which has about 10 million multi-Ethnic populations and represents from the whole country. Methods: In this retrospective study, the measured SCL of 105,128 individuals referred to different laboratories of Tehran, Iran were evaluated and its relationship with the age, gender, seasons, and different years during 2009-2018, were analyzed. Results: After excluding outliers, 91,257samples remained, which 61162 (58.64%) and 30,095 (41.36%) were female and male, respectively.  The mean SCL was 9.36 (9.35, 9.37) mg/dl (95%CI). The highest and lowest SCLs were 3.1 and 18.2mg/dl, respectively. From the total study population, 74127 (81.23%) had normal SCLs, 14110 (15.46%) had hypocalcemia, and 3020 (3.31%) had hypercalcemia. SCLs were normal in 83.6% of men and 79.66% of women. Women had a significantly higher frequency of hypocalcemia compared to men (17.2% vs. 12.83%, p<0.0001). Conclusion: Normal and abnormal SCLs were significantly different in age groups and in both genders. It means that gender and age affect SCLs. Every year of increasing age, reduces the chance of hypercalcemia by 40%, significantly. Age seems to affect hypercalcemia more than hypocalcemia. Age in men increases the risk of hypocalcemia, and reduces the risk of hypocalcemia in women. Therefore, it is recommended to encourage dietary calcium intake among premenopausal women and older men.